Essays On Otherness. - Laplanche, Jean (Warwick studies in European philosophy., 1998)
Since the death of Jacques Lacan, Jean Laplanche is now considered to be one of the worlds foremost psychoanalytic thinkers. In spite of the influence of his work over the last thirty years, remarkably little has been available in English. Essays On Othe.